The analysis of health care expenses of Turkey between 1990-2012 - (:unkn) unknown (IGI Global, 2015)
Health is described not only as the absence of disease and disability but also as physically, psychologically, and socially general Well-Being of people. Best practices of individuals and the society from the health services depend on taking the correct decisions on health policies. In addition, the thought that a country spending much on health services must have a perfect status of health should not be perceived as right. Effectiveness of the spending result in the efficient practices of these services. Although there have been many institutions carrying out the health services, it has been observed that the share separated for the health from the gross domestic product in Turkey increased until 2009 but decreased as of the mentioned year and it has been stated as low compared with the other countries. In this chapter the effectiveness of Turkey's health spending between 1999 and 2012 has been analysed from this view. © 2015, IGI Global. All rights reserved.